Analysis of Spanish generic medicines retail market: recommendations to enhance long-term sustainability. (June 2014) - Dylst, Pieter; Vulto, Arnold G; Simoens, Steven
<x xml:space="preserve">Abstract</x> The use of generic medicines in Spain is traditionally low compared to other European countries, despite efforts of the Spanish government in the past. This paper provides a perspective on the Spanish generic medicines retail market and how the current policy environment may affect the long-term sustainability. The Spanish government's focus on prices of generic medicines (e.g., mandatory price cuts, reference price set at the lowest level) have made them amongst the lowest in Europe. In our opinion, this combination of continuous pressure on prices and limited diffusion of generic medicines may undermine the long-term sustainability of the Spanish generic medicines retail market. The unique experience in Spain shows the impact of demand-side policies on the use of generic medicines. Because a sustainable generic medicines retail market is important to maintain future competition in the off-patent medicines market, this perspective paper rounds off with recommendations to increase its sustainability.